UTILIZATION OF IT AND THE EFFECT ON INDIVIDUAL PERFORMANCE OF LECTURERS AT STATE POLYTECHNIC SRIWIJAYA - Irma Salamah (Universitas Hayam Wuruk Perbanas, 2012)
Recently, the use of personal computers has widespread worldwide, both college and nonamong college. In the entire universities, using personal computers has been practiced optimallyby the lecturers in order to provide a positive impact on their individual performance.This study is aimed at examining and analyzing the utilization factors of information technologyand its influence towards the performance of lecturers in terms of utilizing their personalcomputer (PC). The factors being analyzed were social factors, affective (feelings of the individual),complexity, job appropriateness, long-term consequences, and facilitating conditions.The research sample consists of 79 lecturers in the State Polytechnic of Sriwijaya.These data were collected and used to predict the factors of utilization of information technologyon the lecturers’ performance. It was found out that there was a negative relationshipand not significant for social factors, affective (feelings of the individual), complexity, andjob appropriateness, whereas long-term consequences and utilizations of IT. The facilitatingconditions were found to have a positive and significant relationship towards the performanceof the individual performance.